2022
DOI: 10.29240/ef.v6i1.4210
|View full text |Cite
|
Sign up to set email alerts
|

Using A Cognitive Therapy to Enhance Slow Learners’ Competence: Teacher’s Strategy

Abstract: The purpose of this study is to look at the capacity of slow learners in elementary school to improve their memory using cognitive therapy. The study was carried out at SDLB Gunung Louser Gayo Lues, the key organizer of inclusion. This study's sample consisted of pupils who are classified as slow learners among children with special needs (slow learners). This study's sample size was 20 students. In qualitative research, data is collected in natural settings and from original sources. More participatory observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[13] found that through kinetic sand games, it was considered to be able to develop cognitive, social skills, motor skills, and craft creation abilities. [14] found that the cognitive treatment given could stimulate the ability of slow learners in developing their memory skills. [15] found that memorizing Qur'an could increase effectiveness to improve functional communication skills.…”
Section: State Of the Artmentioning
confidence: 99%
“…[13] found that through kinetic sand games, it was considered to be able to develop cognitive, social skills, motor skills, and craft creation abilities. [14] found that the cognitive treatment given could stimulate the ability of slow learners in developing their memory skills. [15] found that memorizing Qur'an could increase effectiveness to improve functional communication skills.…”
Section: State Of the Artmentioning
confidence: 99%